Technical Advances to Study Extracellular Vesicles - Carpintero-Fernández, Paula; Fafián-Labora, Juan; O'Loghlen, Ana (Frontiers in Molecular Biosciences, 2017)
Extracellular vesicles are a heterogeneous and dynamic group of bi-lipid membrane nanoparticles that can be classified into three different groups depending on their cellular origin: exosomes, microvesicles and apoptotic bodies. They are produced by different cell types and can be isolated from almost all body fluids. EVs contain a variety of proteins, lipids, nucleic acids and metabolites which regulate a number of biological and pathological scenarios both locally and systemically. Different techniques have been described in order to determine EV isolation, release, uptake and cargo. Although standard techniques such as immunoblotting, fluorescent microscopy and electron microscopy are still being used to characterise and visualise EVs, in the last years, more fine-tuned techniques are emerging. For example, EV uptake can be specifically determined at a single cell level using the Cre reporter methodology and bioluminescence based-methods reports have been employed to determine both EV release and uptake. In addition, techniques for cargo identification have also enormously evolved during these years. Classical mass spectrometry and next generation sequencing have been used in the past, but nowadays, advances in these tools have facilitated a more in depth characterisation of the EV content. In this review, we aim to assess the standard and latest technical advances for studying EV biology in different biological systems.